Negative electrode material and preparation method thereof, negative electrode sheet and battery
By combining MOFs-based composite materials with graphite, a lithium-ion battery negative electrode material with high energy density and strong fast charging capability was prepared, which solved the problem of low energy density of negative electrode materials in the prior art, and achieved high energy density and excellent fast Charge performance.
Patent Information
- Application Number
- CN202310580805.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-22
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-05-22
AI Technical Summary
The energy density of existing lithium-ion battery negative electrode materials is low and cannot meet the needs of high-power equipment such as new energy vehicles.
The negative electrode material formed by combining MOFs-based composite material with graphite. The inorganic metal center of the MOFs-based composite material is Fe, and the ligand is terephthalic acid and phosphomolybdate, which has an octahedral structure and is treated by oscillation and spraying. Preparation by drying.
The energy density and fast charging capability of the negative electrode material are improved, and have excellent rate performance and environmentally friendly preparation method.
Smart Images

Figure CN116504945B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode material and a preparation method thereof, a negative electrode sheet and a battery. Background Art
[0002] In recent years, with the continuous development of energy storage technology, energy storage devices such as lithium-ion batteries (LIBs) are not only widely used in portable devices such as laptops and mobile phones, but also play an irreplaceable role in aerospace, new energy vehicles, and power grids. With the continuous expansion of the lithium-ion battery market and the continuous expansion of its application areas, different requirements have been put forward for lithium-ion batteries, such as low-temperature resistant batteries, fast-charging batteries, and high-rate batteries. Among the many components of lithium-ion batteries, electrode materials are an important component, which determines the performance and application areas of the battery. The commonly used negative electrode material for lithium-ion batteries on the market is low-capacity graphite (372mAh g -1 ), so the battery energy density is low and cannot meet the needs of high-power equipment such as new energy vehicles.
[0003] In view of this, the present invention is proposed. Summary of the invention
[0004] An object of the present invention is to provide a negative electrode material having excellent capacity, good conductivity and excellent lithium storage performance.
[0005] Another object of the present invention is to provide a method for preparing the negative electrode material, which is environmentally friendly and can obtain a negative electrode material with excellent electrochemical properties.
[0006] Another object of the present invention is to provide a negative electrode sheet.
[0007] Another object of the present invention is to provide a battery having high energy density and excellent fast charging capability.
[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0009] A negative electrode material, comprising a MOFs-based composite material and graphite, wherein the inorganic metal center of the MOFs-based composite material is Fe, and the ligands are terephthalic acid and phosphomolybdic acid; the MOFs-based composite material has an octahedral structure;
[0010] The mass ratio of the MOFs-based composite material to the graphite is (1-50):100.
[0011] In one embodiment, the particle size of the MOFs-based composite material is 300 nm to 5 μm.
[0012] In one embodiment, the specific capacity of the MOFs-based composite material is 600 to 1500 mAh / g.
[0013] In one embodiment, the specific surface area of the negative electrode material is 1 to 5 m 2 / g.
[0014] In one embodiment, the specific capacity of the negative electrode material is 400 to 800 mAh / g.
[0015] The method for preparing the negative electrode material comprises the following steps:
[0016] The mixed system of MOFs-based composite material, graphite and alcohol solvent is subjected to oscillation treatment and then spray-dried to obtain the negative electrode material.
[0017] In one embodiment, the method for preparing the MOFs-based composite material comprises the following steps:
[0018] (a) subjecting a mixture of iron salt, phosphomolybdic acid and water to a first stirring treatment to obtain a first solution;
[0019] (b) subjecting the mixture of terephthalic acid and the first alcohol solvent to a first heat treatment and a second stirring treatment to obtain a second solution;
[0020] (c) maintaining the temperature of the second solution, adding the first solution obtained in step (a) dropwise to the second solution to obtain a third solution; subjecting the third solution to a second heat treatment, and then performing solid-liquid separation, collecting the solids, washing them, and drying them to obtain a MOFs-based composite material;
[0021] There is no order of precedence for step (a) and step (b).
[0022] In one embodiment, the mass ratio of the iron salt, the phosphomolybdic acid and the terephthalic acid is (0.1-1):(0.1-1):(0.1-1).
[0023] In one embodiment, the ratio of the total mass of the iron salt and phosphomolybdic acid to the water is (0.2-2) g: (10-30) mL.
[0024] In one embodiment, the usage ratio of the terephthalic acid and the first alcohol solvent is (0.1-1) g: (10-30) mL.
[0025] In one embodiment, the iron salt includes at least one of ferric chloride, ferric sulfate, and ferric nitrate.
[0026] In one embodiment, the rotation speed of the first stirring process is 100 to 800 r / min, and the time of the first stirring process is 10 to 30 min.
[0027] In one embodiment, the first alcohol solvent includes at least one of methanol, ethanol, ethylene glycol, propanol, glycerol, butanol, pentanol, hexanol, heptanol and octanol.
[0028] In one embodiment, the temperature of the first heat treatment is 50-80°C.
[0029] In one embodiment, the rotation speed of the second stirring treatment is 100 to 800 r / min, and the time of the second stirring treatment is magnetic stirring for 10 to 30 minutes.
[0030] In one embodiment, the first solution is uniformly added dropwise to the second solution at a rate of 50 to 100 μL / min.
[0031] In one embodiment, during the process of adding the first solution dropwise to the second solution, the second solution is subjected to a third stirring treatment, and the rotation speed of the third stirring treatment is 100 to 800 r / min.
[0032] In one embodiment, after the first solution is added dropwise, stirring is continued for 10 to 60 minutes.
[0033] In one embodiment, the temperature of the second heat treatment is 50-200° C., and the time of the second heat treatment is 6-72 hours.
[0034] In one embodiment, the washing agent used in the washing includes N,N-dimethylformamide and a second alcohol solvent; the second alcohol solvent includes at least one of methanol, ethanol, ethylene glycol, propanol, glycerol, butanol, pentanol, hexanol, heptanol and octanol.
[0035] In one embodiment, the drying comprises vacuum drying; the drying temperature is 45 to 60° C.; the drying vacuum degree is -0.08 to -0.12 MPa.
[0036] In one embodiment, the mass ratio of the MOFs-based composite material, graphite and alcohol solvent is (1-50):100:(180-220).
[0037] In one embodiment, the shaking treatment time is 5 to 240 minutes.
[0038] In one embodiment, the inlet temperature of the spray drying is 170-250°C, and the outlet temperature is 80-130°C.
[0039] A negative electrode sheet comprises the negative electrode material or the negative electrode material prepared by the negative electrode material preparation method.
[0040] A battery comprises the negative electrode sheet.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] (1) The present invention uses phosphomolybdic acid (PMo 12 ) is doped into the MIL-88B octahedron in a coordinated manner, which can not only improve the conductivity of MIL-88B, but also provide more redox sites, thereby improving the lithium storage of MIL-88B; the present invention is to dope MIL-88B-PMo 12 The composite material is combined with graphite to obtain a negative electrode material with high energy density and good fast charging capability.
[0043] (2) The method of the present invention is more environmentally friendly and has low cost. The obtained negative electrode material has high energy density and good fast charging capability.
[0044] (3) The battery of the present invention has excellent rate performance and fast charging capability. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0046] Figure 1 This is a scanning electron microscope image of the MOFs-based composite material in Example 1 of the present invention;
[0047] Figure 2 This is an energy spectrum analysis diagram of the MOFs-based composite material in Example 1 of the present invention. DETAILED DESCRIPTION
[0048] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0049] According to one aspect of the present invention, the present invention relates to a negative electrode material, comprising a MOFs-based composite material and graphite, wherein the inorganic metal center of the MOFs-based composite material is Fe, and the ligands are terephthalic acid and phosphomolybdic acid; the MOFs-based composite material has an octahedral structure;
[0050] The mass ratio of the MOFs-based composite material to the graphite is (1-50):100.
[0051] The MOFs-based composite material (MIL-88B-PMo 12 ) is an octahedral particle with high structural stability, which can effectively alleviate its own expansion during charging and discharging, improve the stability of the electrode, and this structure can shorten the transmission path of Li+, accelerate ion transmission, and improve rate performance; the present invention converts phosphomolybdic acid (PMo 12 ) is doped into the MIL-88B octahedron in a coordinated manner, which can not only improve the conductivity of MIL-88B, but also provide more redox sites, which can improve the lithium storage of MIL-88B; in one embodiment, the C, O, Fe, P and Mo elements of the MOFs-based composite material are uniformly distributed in the octahedron. 12 The composite material and graphite are combined to obtain a negative electrode material with high energy density and good fast charging capability. 12 The composite material and graphite particles are evenly distributed.
[0052] In one embodiment, the particle size of the MOFs-based composite material is 300 nm to 5 μm, for example, 300 nm, 500 nm, 800 nm, 900 nm, 1 μm, 1.5 μm, 2 μm, 3 μm, 4 μm or 5 μm.
[0053] In one embodiment, the specific capacity of the MOFs-based composite material is 600 to 1500 mAh / g, for example 600 mAh / g, 700 mAh / g, 800 mAh / g, 900 mAh / g, 1000 mAh / g, 1100 mAh / g, 1200 mAh / g, 1300 mAh / g, 1400 mAh / g, 1500 mAh / g, etc.
[0054] In one embodiment, the specific surface area of the negative electrode material is 1 to 5 m 2 / g,1m 2 / g, 1.5m 2 / g, 2m 2 / g, 2.5m 2 / g, 3m 2 / g, 3.5m 2 / g, 4m 2 / g, 4.5m 2 / g, 5m 2 / g, etc.
[0055] In one embodiment, the specific capacity of the negative electrode material is 400-800mAh / g, for example 400mAh / g, 450mAh / g, 500mAh / g, 550mAh / g, 600mAh / g, 650mAh / g, 700mAh / g, 750mAh / g, 800mAh / g, etc.
[0056] The method for preparing the negative electrode material as described above comprises the following steps:
[0057] The mixed system of MOFs-based composite material, graphite and alcohol solvent is subjected to oscillation treatment and then spray-dried to obtain the negative electrode material.
[0058] The preparation method of the negative electrode material of the present invention is simple and easy, and the obtained negative electrode material has high capacity density and excellent fast charging capability.
[0059] In one embodiment, the method for preparing the MOFs-based composite material comprises the following steps:
[0060] (a) subjecting a mixture of iron salt, phosphomolybdic acid and water to a first stirring treatment to obtain a first solution;
[0061] (b) subjecting the mixture of terephthalic acid and the first alcohol solvent to a first heat treatment and a second stirring treatment to obtain a second solution;
[0062] (c) maintaining the temperature of the second solution, adding the first solution obtained in step (a) dropwise to the second solution to obtain a third solution; subjecting the third solution to a second heat treatment, and then performing solid-liquid separation, collecting the solids, washing them, and drying them to obtain a MOFs-based composite material;
[0063] There is no order of precedence for step (a) and step (b).
[0064] PMo 12 It is composed of a central PO4 tetrahedron and a typical molybdenum oxide (MoO6) octahedral cluster cage, in which the Mo element is in a highly oxidized state. 6+ Restored to Mo 2+ , which gives the material a higher capacity. But PMo 12 It is not competitive in coordination and is difficult to coordinate with Fe 3+ The present invention introduces an alcohol solvent into the reaction system through the above method, and utilizes the esterification reaction between terephthalic acid and alcohol to reduce the reactivity of terephthalic acid, thereby increasing the activity of phosphomolybdate [PMo 12 O 40 ] 3- and Fe 3+ The coordination of PMo 12Doping into iron-based MOFs (MIL-88B) in the form of coordination can improve the conductivity and capacity of MOFs-based composite materials and improve lithium storage performance. The method of the invention can avoid the use of toxic polar solvents (N,N-dimethylformamide, etc.), is more environmentally friendly and low-cost.
[0065] In one embodiment, the mass ratio of the iron salt, the phosphomolybdic acid and the terephthalic acid is (0.1-1): (0.1-1): (0.1-1), such as 0.1:0.1:0.1, 0.1:0.1:0.3, 0.4:0.4:0.5, 0.5:0.5:0.7, 0.8:0.8:1, etc. The iron salt, phosphomolybdic acid and terephthalic acid of the present invention are within a suitable usage ratio range, which is more conducive to obtaining a MOFs-based composite material with excellent conductivity and high capacity.
[0066] In one embodiment, the total mass ratio of the iron salt and phosphomolybdic acid to the water is (0.2-2) g: (10-30) mL, for example, 0.2 g: 10 mL, 0.5: 15 mL, 1 g: 20 mL, 2 g: 30 mL, etc.
[0067] In one embodiment, the usage ratio of the terephthalic acid and the first alcohol solvent is (0.1-1) g: (10-30) mL, for example, 0.1 g: 10 mL, 0.5: 15 mL, 1 g: 20 mL, 2 g: 30 mL, etc.
[0068] In one embodiment, the mass ratio of the MOFs-based composite material, graphite and alcohol solvent (such as ethanol) is (1-50):100:(180-220), for example (1-50):100:200, for example 10:100:200, 20:100:200, 30:100:200, 50:100:200, etc.
[0069] In one embodiment, the iron salt of the present invention is a soluble iron salt, and the iron salt includes at least one of ferric chloride, ferric sulfate and ferric nitrate.
[0070] In one embodiment, the stirring speed of the first treatment is 100-800 r / min, such as 100 r / min, 200 r / min, 300 r / min, 400 r / min, 500 r / min, 600 r / min, 700 r / min, 800 r / min, etc. The stirring time is 10-30 min, such as 10 min, 15 min, 20 min, 25 min, 30 min, etc. The present invention is more conducive to uniform mixing through appropriate stirring speed and stirring time.
[0071] In one embodiment, the first alcohol solvent includes at least one of methanol, ethanol, ethylene glycol, propanol, glycerol, butanol, pentanol, hexanol, heptanol and octanol.
[0072] In one embodiment, the temperature of the first heat treatment is 50-80°C, for example, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, etc.
[0073] In one embodiment, the rotation speed of the second stirring treatment is 100-800 r / min, for example, 100 r / min, 200 r / min, 300 r / min, 400 r / min, 500 r / min, 600 r / min, 700 r / min, 800 r / min, etc.; the time of the second stirring treatment is magnetic stirring for 10-30 min, for example, 10 min, 15 min, 20 min, 25 min, 30 min, etc.
[0074] In one embodiment, the first solution is uniformly added to the second solution at a dropping speed of 50 to 100 μL / min, such as 50 μL / min, 60 μL / min, 70 μL / min, 80 μL / min, 90 μL / min or 100 μL / min, etc. The present invention is more conducive to the reaction by uniformly adding the first solution to the second solution at a suitable dropping speed, thereby forming a MOFs-based composite material with stable structure, good conductivity and high capacity.
[0075] In one embodiment, during the process of adding the first solution dropwise to the second solution, the second solution is subjected to a third stirring treatment, and the rotation speed of the third stirring treatment is 100 to 800 r / min, for example, 100 r / min, 200 r / min, 300 r / min, 400 r / min, 500 r / min, 600 r / min, 700 r / min, 800 r / min, etc.
[0076] In one embodiment, after the first solution is added dropwise, stirring is continued for 10 to 60 minutes, for example, 10 minutes, 20 minutes, 30 minutes, 40 minutes, 50 minutes, 60 minutes, etc.
[0077] In one embodiment, the temperature of the second heat treatment is 50-200°C, for example, 50°C, 60°C, 80°C, 100°C, 120°C, 150°C, 200°C, etc.; the time of the second heat treatment is 6-72h, for example, 6h, 8h, 10h, 12h, 15h, 20h, 25h, 30h, 50h, 60h, 72h, etc.
[0078] In one embodiment, the washing agent used in the washing comprises N,N-dimethylformamide and a second alcohol solvent; the second alcohol solvent comprises at least one of methanol, ethanol, ethylene glycol, propanol, glycerol, butanol, pentanol, hexanol, heptanol and octanol. The washing is performed 2 to 5 times with N,N-dimethylformamide and the second alcohol solvent respectively to remove the residual terephthalic acid.
[0079] In one embodiment, the drying comprises vacuum drying; the drying temperature is 45 to 60°C, such as 45°C, 48°C, 50°C, 55°C or 60°C; the drying vacuum degree is -0.08 to -0.12 MPa.
[0080] In one embodiment, the oscillation treatment time is 5 to 240 min, such as 5 min, 8 min, 10 min, 15 min, 20 min, 25 min, 30 min, 50 min, 60 min, 100 min, 150 min or 240 min, etc. The present invention adopts oscillation treatment for a suitable time, which is more conducive to the mixing of materials.
[0081] In one embodiment, the inlet temperature of the spray drying is 170-250°C, such as 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, etc. The outlet temperature is 80-130°C, such as 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, etc. The present invention adopts appropriate inlet temperature and outlet temperature, which is more conducive to the drying and mixing of materials.
[0082] According to another aspect of the present invention, the present invention also relates to a negative electrode sheet, comprising the negative electrode material or the negative electrode material prepared by the method for preparing the negative electrode material.
[0083] According to another aspect of the present invention, the present invention also relates to a battery, comprising the negative electrode sheet.
[0084] The battery of the present invention has excellent rate performance and fast charging capability.
[0085] The following is further explained in conjunction with specific embodiments.
[0086] Example 1
[0087] A method for preparing a negative electrode material comprises the following steps:
[0088] Step 1: Mix 0.5 g of iron salt and 0.5 g of phosphomolybdic acid (PMo 12 ) was dissolved in 10 mL of deionized water and magnetically stirred at 500 r / min for 10 min to obtain a first solution;
[0089] Step 2: Add 0.5 g of terephthalic acid into 30 mL of ethanol solution, cover with plastic wrap, heat to 60°C, and stir magnetically at 500 r / min for 30 min to obtain a second solution;
[0090] Step 3: maintaining the temperature of the second solution, uniformly adding the first solution to the second solution at a speed of 80 μL / s while magnetically stirring at a speed of 500 r / min, and after the first solution is completely added, continuing stirring for 60 min to obtain a third solution;
[0091] Step 4: The third solution was transferred to a 100 mL polytetrafluoroethylene liner, and then placed in a stainless steel autoclave, maintained at 120 ° C for 12 h, and naturally cooled to room temperature to obtain a brown-yellow precipitate. The precipitate was washed alternately with N, N-dimethylformamide (DMF) solution and ethanol solution for 3 times each to remove residual terephthalic acid, and then dried at 50 ° C overnight in vacuum (-0.1 MPa) to obtain (MIL-88B)-PMo 12 Octahedral composites;
[0092] Step 5: (MIL-88B)-PMo 12 The octahedral composite material, graphite and ethanol were mixed in a mass ratio of 10:100:200, shaken for 120 min, and spray-dried to obtain (MIL-88B)-PMo 12 / graphite composite negative electrode material.
[0093] Example 2
[0094] A method for preparing a negative electrode material comprises the following steps:
[0095] Step 1: Mix 0.5 g of iron salt and 0.5 g of phosphomolybdic acid (PMo 12 ) was dissolved in 10 mL of deionized water and magnetically stirred at 500 r / min for 10 min, which was recorded as the first solution;
[0096] Step 2: Add 0.5 g of terephthalic acid into 30 mL of methanol solution, cover with plastic wrap, heat to 60°C, and stir magnetically at 500 r / min for 30 min, which is recorded as the second solution;
[0097] Step 3: Keep the temperature of the second solution, and uniformly add the first solution to the second solution at a speed of 80 μL / s while magnetically stirring at a speed of 500 r / min. After the first solution is completely added, continue stirring for 60 minutes, which is recorded as the third solution;
[0098] Step 4: The third solution was transferred to a 100 mL polytetrafluoroethylene liner, and then placed in a stainless steel autoclave, maintained at 120 ° C for 16 h, and naturally cooled to room temperature to obtain a brown-yellow precipitate. The precipitate was washed alternately with N, N-dimethylformamide (DMF) solution and methanol solution for 3 times each to remove residual terephthalic acid, and then dried at 50 ° C overnight in vacuum (~-0.1 MPa) to obtain (MIL-88B)-PMo 12 Octahedral composites;
[0099] Step 5: (MIL-88B)-PMo 12 The octahedral composite material, graphite and ethanol were mixed in a mass ratio of 10:100:200, shaken for 120 min, and spray-dried to obtain (MIL-88B)-PMo 12 / graphite composite negative electrode material.
[0100] Example 3
[0101] A method for preparing a negative electrode material comprises the following steps:
[0102] Step 1: Mix 0.4 g of iron salt and 0.4 g of phosphomolybdic acid (PMo 12 ) was dissolved in 10 mL of deionized water and magnetically stirred at 500 r / min for 10 min to obtain a first solution;
[0103] Step 2: Add 0.6 g of terephthalic acid into 30 mL of ethanol solution, cover with plastic wrap, heat to 60°C, and stir magnetically at 500 r / min for 30 min to obtain a second solution;
[0104] Step 3: maintaining the temperature of the second solution, uniformly adding the first solution to the second solution at a speed of 80 μL / s while magnetically stirring at a speed of 500 r / min, and after the first solution is completely added, continuing stirring for 60 min to obtain a third solution;
[0105] Step 4: The third solution was transferred to a 100 mL polytetrafluoroethylene liner, and then placed in a stainless steel autoclave, maintained at 150 ° C for 12 h, and naturally cooled to room temperature to obtain a brown-yellow precipitate. The precipitate was washed alternately with N, N-dimethylformamide (DMF) solution and ethanol solution for 3 times each to remove residual terephthalic acid, and then dried at 50 ° C overnight in vacuum (-0.1 MPa) to obtain (MIL-88B)-PMo 12 Octahedral composites;
[0106] Step 5: (MIL-88B)-PMo 12 The octahedral composite material, graphite and ethanol were mixed in a mass ratio of 20:100:200, shaken for 120 min, and spray-dried to obtain (MIL-88B)-PMo12 / graphite composite negative electrode material.
[0107] Example 4
[0108] A method for preparing a negative electrode material comprises the following steps:
[0109] Step 1: Mix 0.4 g of iron salt and 0.4 g of phosphomolybdic acid (PMo 12 ) was dissolved in 10 mL of deionized water and magnetically stirred at 500 r / min for 10 min to obtain a first solution;
[0110] Step 2: Add 0.6 g of terephthalic acid into 30 mL of ethanol solution, cover with plastic wrap, heat to 60°C, and stir magnetically at 500 r / min for 30 min, which is recorded as the second solution;
[0111] Step 3: maintaining the temperature of the second solution, uniformly adding the first solution to the second solution at a speed of 80 μL / s while magnetically stirring at a speed of 500 r / min, and after the first solution is completely added, continuing stirring for 60 min to obtain a third solution;
[0112] Step 4: The third solution was transferred to a 100 mL polytetrafluoroethylene liner, and then placed in a stainless steel autoclave, maintained at 150 ° C for 24 h, and naturally cooled to room temperature to obtain a brown-yellow precipitate. The precipitate was washed alternately with N, N-dimethylformamide (DMF) solution and ethanol solution for 3 times each to remove residual terephthalic acid, and then dried at 50 ° C overnight in vacuum (-0.1 MPa) to obtain (MIL-88B)-PMo 12 Octahedral composites;
[0113] Step 5: (MIL-88B)-PMo 12 The octahedral composite material, graphite and ethanol were mixed in a mass ratio of 30:100:200, shaken for 120 min, and spray-dried to obtain (MIL-88B)-PMo 12 / graphite composite negative electrode material.
[0114] Comparative Example 1:
[0115] A negative electrode material, except (MIL-88B)-PMo 12 The mass ratio of the octahedral composite material to graphite is 75:100, and other conditions are the same as those in Example 4.
[0116] Comparative Example 2
[0117] A negative electrode material, except (MIL-88B)-PMo 12 The mass ratio of the octahedral composite material to graphite is 0.5:100, and other conditions are the same as those in Example 4.
[0118] Experimental example
[0119] 1. Graph Analysis
[0120] The (MIL-88B)-PMo obtained in Example 1 12 Octahedral composite materials were characterized, and the scanning electron microscope images were shown in Figure 1 As shown, it can be seen that the material has an octahedral structure and a particle size of about 300nm. Figure 2 As shown, it can be seen that the material contains C, O, Fe, P, and Mo elements, indicating that PMo 12 Successfully doped into MIL-88B.
[0121] 2. Battery performance test
[0122] 1. The negative electrode materials prepared in Examples 1 to 4 and Comparative Example 1 were respectively prepared into lithium-ion batteries. -1 The charge and discharge were carried out at the current density 2400, and the capacity obtained in the 1st cycle and the 500th cycle was tested. The results are shown in Table 1.
[0123] Table 1 Capacity results of each battery at the 1st and 500th cycles
[0124]
[0125]
[0126] 2. The batteries prepared in Examples 1 to 4 and Comparative Example 1 were charged and discharged at different current densities, and the average charging capacity was tested 10 times. The results are shown in Table 2.
[0127] Table 2 Average charging capacity results (mAh g -1 )
[0128]
[0129] It can be seen from Table 1 that the negative electrode material of the present invention is applied to lithium-ion batteries at 200 mA g -1 After 500 cycles at the current density, the charge capacity is 395 mAh g -1 Above, it has a higher energy density. As can be seen from Table 2, the negative electrode material of the present invention has excellent rate performance, and can still maintain a high capacity even at a current density of 3A / g, indicating that the negative electrode material of the present invention has excellent fast charging capability. The coulombic efficiency and cycle performance of the battery prepared by the negative electrode material of Comparative Example 1 are relatively poor, and the fast charging capability is relatively poor. The cycle performance and rate performance of the battery prepared by the negative electrode material of Comparative Example 2 are relatively poor, and the capacity is low.
[0130] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A negative electrode material, characterized in that: It comprises a MOFs-based composite material and graphite, wherein the inorganic metal center of the MOFs-based composite material is Fe, and the ligands are terephthalic acid and phosphomolybdic acid; the MOFs-based composite material has an octahedral structure; The mass ratio of the MOFs-based composite material to the graphite is (1-50):100; The method for preparing the negative electrode material, The following steps are involved: The mixed system of MOFs-based composite material, graphite and alcohol solvent is subjected to oscillation treatment, and then spray-dried to obtain a negative electrode material; The preparation method of the MOFs-based composite material comprises the following steps: (a) subjecting a mixture of iron salt, phosphomolybdic acid and water to a first stirring treatment to obtain a first solution; (b) subjecting the mixture of terephthalic acid and the first alcohol solvent to a first heat treatment and a second stirring treatment to obtain a second solution; (c) maintaining the temperature of the second solution, and adding the first solution obtained in step (a) dropwise to the second solution to obtain a third solution; subjecting the third solution to a second heat treatment, and then performing solid-liquid separation, collecting the solid, washing, and drying the solid, to obtain a MOFs-based composite material; There is no order of precedence for step (a) and step (b).
2. The negative electrode material according to claim 1, characterized in that Contains at least one of the following features (1) to (2): (1) The particle size of the MOFs-based composite material is 300 nm to 5 μm; (2) The specific capacity of the MOFs-based composite material is 600~1500mAh / g.
3. The negative electrode material according to claim 1, characterized in that Contains at least one of the following features (1) to (2): (1) The specific surface area of the negative electrode material is 1~5m 2 / g; (2) The specific capacity of the negative electrode material is 400-800 mAh / g.
4. The negative electrode material according to claim 1, characterized in that Contains at least one of the following features (1) to (8): (1) The mass ratio of the iron salt, the phosphomolybdic acid and the terephthalic acid is (0.1-1): (0.1-1): (0.1-1); (2) The total mass of the iron salt and phosphomolybdic acid to the water is in a ratio of (0.2-2) g: (10-30) mL; (3) The usage ratio of the terephthalic acid and the first alcohol solvent is (0.1-1) g: (10-30) mL; (4) the iron salt comprises at least one of ferric chloride, ferric sulfate and ferric nitrate; (5) The speed of the first stirring treatment is 100-800 r / min, and the time of the first stirring treatment is 10-30 min; (6) the first alcohol solvent comprises at least one of methanol, ethanol, ethylene glycol, propanol, glycerol, butanol, pentanol, hexanol, heptanol and octanol; (7) The temperature of the first heat treatment is 50-80°C; (8) The rotation speed of the second stirring treatment is 100-800 r / min, and the time of the second stirring treatment is magnetic stirring for 10-30 min.
5. The negative electrode material according to claim 1, characterized in that Contains at least one of the following features (1) to (6): (1) uniformly adding the first solution dropwise to the second solution at a rate of 50 to 100 μL / min; (2) in the process of adding the first solution dropwise to the second solution, performing a third stirring treatment on the second solution, wherein the rotation speed of the third stirring treatment is 100-800 r / min; (3) After the first solution is added dropwise, continue stirring for 10 to 60 minutes; (4) The temperature of the second heat treatment is 50-200°C, and the time of the second heat treatment is 6-72h; (5) The washing agent used in the washing comprises N,N-dimethylformamide and a second alcohol solvent; the second alcohol solvent comprises at least one of methanol, ethanol, ethylene glycol, propanol, glycerol, butanol, pentanol, hexanol, heptanol and octanol; (6) The drying includes vacuum drying; the drying temperature is 45~60°C; the drying vacuum degree is -0.08~-0.12MPa.
6. The negative electrode material according to claim 1, characterized in that: Contains at least one of the following features (1) to (3): (1) The mass ratio of the MOFs-based composite material, graphite and alcohol solvent is (1-50):100:(180-220); (2) The shaking treatment time is 5 to 240 minutes; (3) The inlet temperature of the spray drying is 170-250°C, and the outlet temperature is 80-130°C.
7. A negative electrode sheet, characterized in that: The negative electrode material comprises the negative electrode material according to any one of claims 1 to 6.
8. A battery, characterized in that: Includes the negative electrode sheet as described in claim 7.
Citation Information
Patent Citations
Preparation method and application of composite material containing graphite and MOF
CN112679966A